The effect of capital and competence on micro enterpriser performance in Siranindi - ., Abidin; ., Rusni (Opción, 2020)
This study aims to analyze the effect of capital and competence on micro enterpriser performance in Siranindi village. This research is a verification study using a quantitative approach. The research results showed that capital has a partial and significant effect on the micro enterpriser performance and competence has a partial and significant effect on the micro enterpriser performance. In conclusion, in Islamic economics perception, capital and competence have a significant effect both partially and simultaneously on micro enterprisers’ performance in the Siranindi Village, West Palu District.